2019
DOI: 10.1039/c9ra05980f
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cr(vi) from wastewater by a two-step method of oxalic acid reduction-modified fly ash adsorption

Abstract: Removal of Cr(vi) from wastewater using a two-step method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Thus, they concluded that Mn(II) could catalyze the reduction process of Cr(VI) with oxalic acid. Many methods had been developed to promote the reduction process of Cr(VI) with oxalic acid, like catalyzed by TiO 2 , Al 2 O 3 , FeOOH and sunlight 22 25 , but these methods were still not easy for the practical application, especially in groundwater remediation. This paper focused on the directional reduction behavior of Cr(VI) with oxalic acid because of the direct Cr(VI) reduction by oxalic acid was thermodynamically spontaneous 26 28 , the effect of dosage of oxalic acid, reaction temperature, dosage of sulfuric acid and reaction time on the reduction efficiency of Cr(VI) were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they concluded that Mn(II) could catalyze the reduction process of Cr(VI) with oxalic acid. Many methods had been developed to promote the reduction process of Cr(VI) with oxalic acid, like catalyzed by TiO 2 , Al 2 O 3 , FeOOH and sunlight 22 25 , but these methods were still not easy for the practical application, especially in groundwater remediation. This paper focused on the directional reduction behavior of Cr(VI) with oxalic acid because of the direct Cr(VI) reduction by oxalic acid was thermodynamically spontaneous 26 28 , the effect of dosage of oxalic acid, reaction temperature, dosage of sulfuric acid and reaction time on the reduction efficiency of Cr(VI) were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, at the initial time of contact, there is a large number of vacant adsorption sites and also a high concentration gradient of Cr­(VI) between the adsorbent and the bulk of the solution. As adsorption equilibrium was reached, the adsorption capacity remained unchanged because of the decrease in number of vacant sites available for adsorption and also a decrease in concentration gradient. , The kinetics data for pseudo-first-order and pseudo-second-order kinetic models are displayed in Table . As shown in Figure b, the pseudo-second-order kinetic model better defined the adsorption of Cr­(VI) with R 2 values of 0.9836, 0.9868, and 0.9954 for Cr­(VI) initial concentrations of 20, 50, and 75 mg/L, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The second stage demonstrates that as the concentration gradient driving movement of ions decreases, ammonium ions progressively diffuse into the channels of the BNPP and reach equilibrium. 77,78 The larger k 1d value represents the ratecontrolled intra-particle diffusion process, while the small/ negligible k 2d value indicates that the diffusion rate corresponding to the final equilibrium stage is slow. 78 The larger values of C 2 than C 1 suggest that the diffusion boundary layer during stage 2 became thicker.…”
Section: Elovich Modelmentioning
confidence: 99%
“…77,78 The larger k 1d value represents the ratecontrolled intra-particle diffusion process, while the small/ negligible k 2d value indicates that the diffusion rate corresponding to the final equilibrium stage is slow. 78 The larger values of C 2 than C 1 suggest that the diffusion boundary layer during stage 2 became thicker. 75 The fitting parameters for a two-stage intra-particle diffusion mechanism are consistent with the results showing the possible best fit with pseudo-first-order and pseudo-second-order kinetics and highlight the surface-mediated ammonium ion adsorption process by BNPP.…”
Section: Elovich Modelmentioning
confidence: 99%